(untitled) (The Pakistan Development Review, 1994)
The purpose of this paper is to bring to light the effects of velocity on monetary policy during the process of development. The stated hypothesis is that if velocity declines as per-capita income increases, the monetary authorities can issue more money to finance economic growth with low rates of inflation. This short paper attempts to test the hypothesis in the post 1974 period for the present Pakistan over the period 1974-75 to 1991-92. This period corresponds to the official division of all the financial and other statistics between East and West Pakistan. The financial developments and the trends in overall economic development over the period is expected to yield results different from the studies done in the earlier period.